All-dielectric metasurface for linear-polarization conversion with an arbitrary polarization rotating angle. (January 2023) - Sun, Yuhang; Liu, Yumin; Wu, Tiesheng; Wang, Yu; Li, Jing; Ye, Han; Fan, Hongjie; Wang, Xueyu
Highlights: Arbitrary polarization rotating angle generation. High-efficient linear polarization conversion. Easy customization of polarization angle. High degree of freedom. Abstract: Polarization converters are essential components of optical systems. Here we propose an all-dielectric metasurface linear-polarization converter composed of silicon diatomic nanopillar arrays. The two nanopillars are identical except for the azimuthal angle. The converter can orient the linear polarization to arbitrary angles by changing the two orientation angles of the nanopillars. And the polarization conversion efficiency remains above 90%. The mentioned metasurface is analyzed theoretically and demonstrated by numerical simulation. The results show that the polarization angle of the output wave is exactly equal to the sum of two orientation angles. Thus, the polarization angle of the output wave can be easily controlled. The proposed metasurface breaks the limitation of traditional line polarization converters and may have broad application prospects in wireless communications, imaging systems, and other fields.